2016
DOI: 10.1016/j.jfda.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Studies on physicochemical and nutritional properties of aerial parts of Cassia occidentalis L.

Abstract: In the present, work chemical composition and nutritional value of aerial parts of Cassia occidentalis L. was studied. The aerial parts of C. occidentalis possess favorable physicochemical properties with good nutritional value, such as high energy value, crude fibers, and vitamin levels. The X-ray fluorescence spectrophotometry data revealed that the sample is rich in minerals, especially in Fe, Ca, K, and Mn. Further, minerals such as Mg, Zn, Cu, Na, P, and S are present in good amount and depicted the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Natural antioxidants mainly come from plants in the form of phenolic compounds such as flavonoids and phenolic acids. In vitro and in vivo experiments have shown that phenolic acids exhibit powerful effects on biological responses by scavenging free radicals and eliciting antioxidant capacity [ 41 ]. Phenolic compounds present in P. emodi in previous studies include ethyl gallate, methyl grevillate [ 10 ], benzoic acid, 3-hydroxy benzoic acid [ 8 ], 4-hydroxy benzoic acid, gallic acid, and methyl gallate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidants mainly come from plants in the form of phenolic compounds such as flavonoids and phenolic acids. In vitro and in vivo experiments have shown that phenolic acids exhibit powerful effects on biological responses by scavenging free radicals and eliciting antioxidant capacity [ 41 ]. Phenolic compounds present in P. emodi in previous studies include ethyl gallate, methyl grevillate [ 10 ], benzoic acid, 3-hydroxy benzoic acid [ 8 ], 4-hydroxy benzoic acid, gallic acid, and methyl gallate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on edible plants, such as Glycyrrhiza glabra [42], Allium sativum [43], showed the inhibition of viral replication of SARS-CoV that can be further utilized as leads against SARS-CoV-2, due to similar homology between SARS-CoV and SARS-CoV-2 [44]. Edible antiviral plants like Aloe vera [45], Gingko [46], Olea europaea [47], Cicer arietinum [48], Nigella sativa [49], Agrimonia Pilosa [50], Commelina communis [51], Mangifera indica [52], Syzygium cumini [53] that showed effects against influenza virus Food [106] Human immunodeficiency virus [40] Methanolic leaf extract [40] Inhibiting HIV reverse transcriptase activity [40] 12…”
Section: Plants Inhibiting Viral Replicationmentioning
confidence: 99%
“…Information on the medicinal plants used for the management of liver diseases in the study area is presented in (Manikandaselvi et al, 2016). Several biological activities of S. occidentalis (formerly known as Cassia occidentalis) such as antimicrobial (Hussaini and Deeni, 1991), antimalarial (Tona et al, 2001), anti-inflammatory (Sadique et al, 1987) and anticarcinogenic (sharma et al, 1999) are reported.…”
Section: Plant Species Used For Liver Diseasesmentioning
confidence: 99%